FORMULASI DAN UJI EFEKTIFITAS ANTIOKSIDAN KRIM EKSTRAK ETANOL KORTEKS KAYU JAWA (LANNEA COROMANDELICA HOUT MERR) DENGAN METODE DPPH - Isriany Ismail; Gemy Handayany; Armisman Paturusi; Watri Ratnasari (Universitas Islam Negeri Alauddin Makassar, 2014)
The research has conducted the formulation and Effectiveness Test Ethanol Extract Antioxidant Cream Wood Java cortex (Lannea Coromandelica hout Merr) by DPPH method. This study aims to determine the concentration of the extract java wood (Lannea Coromandelica hout Merr) is effective as an antioxidant for cream formula. Formula cream tested the effectiveness of antioxidants with DPPH. Ethanol extract of the wood cortex java cream formulated in dosage forms by using various concentration of extract 0.03%, 0.3%, 3%. Comparative antioxidant is vitamin C used at a concentration of 0.05%. The test results showed that all the cream formulation has antioxidant activity. Formula cream timber cortex extract Java (Lannea coromandelica Hout Merr) showed antioxidant activity is the most effective formula containing extracts of 3% with the percent inhibition of 55.39% compared with the creamy formula of vitamin C with the percent inhibition of 53.76%.